ANALYSIS OF THE IMPACT OF AIFTA TOWARD INDONESIAN COFFEE EXPORT TO INDIA - maulana luqman firdaus (Mediasi: Journal of International Relations, 2018)
This study aims to explain the Free Trade ASEAN-India cooperation or better known as AIFTA and its impact on Indonesian coffee exports. Specifically this study aims to find out how the impact of ASEAN-India Free Trade Area on Indonesian domestic industry, especially coffee industry. To get the results as mentioned above, the author uses the concept of free trade and the concept of trade in Islam. The Free Trade Concept will analyze how AIFTA's free trade flows have a major impact on Indonesia's coffee export-import cooperation with India. While the concept of trade views in Islam is only limited to how the view of Islam to a relationship of trade between countries. The data analysis techniques using qualitative techniques. The research method that writer use is descriptive research type which aims to know the development and describe in detail a certain social phenomenon. Technique of collecting data is done by literature study which sourced from valid book, journal, document, and website. The results of this study indicate that the enactment of AIFTA, an increase in the export volume of Indonesian coffee to India which has increased and increased. Increased exports can not be separated from the increasing demand for coffee, especially from India, which is the country's main importer of Indonesian coffee. The increase in demand is influenced by the decline in import duties to India post AIFTA. Based on the results of this study, this study can conclude that the implementation of free trade agreement between ASEAN and India brings many positive effects for cooperation between Indonesia and India. The development of research and development of the coffee industry is a good suggestion to improve the performance of the Indonesian coffee industry in competing on the AIFTA framework. Keywords : AIFTA, Export-Import, Industri Kopi, Indonesia, India